Penyerahan Tanah Yang Terikat Dalam Perjanjian Dondon Di Desa Aeklung Kecamatan Doloksanggul Kabupaten Humbang Hasundutan - Silvia Agustina Simamora (Jurnal Perspektif Hukum, 2022)
ABSTRACT The Dondon Agreement is to pawn a plot of rice field land to another party with an agreement that one day the land will be redeemed by the owner and when the land is pawned the land owner will receive the amount of money that the land owner needs from the dondon recipient. Dondon agreements according to customary law have a minimum time limit of 2 years, but in reality what happened in Aeklung village, Doloksanggul district, Humbang Hasundutan district, especially in hamlet I, the people still use the dondon agreement not using the time limit as it should be. The formulation of the problem from this research is how is the mechanism for transferring the dondon agreement in Aeklung village, Doloksanggul district, Humbang Hasundutan district, what are the rights and obligations of the parties who make the dondon agreement, how are the legal protections for the parties who make the dondon agreement. This study uses empirical legal research that is descriptive analytical. The mechanism for the transfer of the dondon agreement in Aeklung village, Doloksanggul sub-district, Humbang Hasundutan Regency, namely party I (dondon giver) and party II (dondon recipient) meet together to make a dondon agreement under sufficient stamp duty witnessed by each party. Based on the agreement, the rights and obligations of the parties arise.